Properties and consolidation of nanocrystalline NbSi2-SiC-Si3N4 composite by pulsed current activated combustion - Bae, Soo-Kyung; Shon, In-Jin; Doh, Jung-Mann; Yoon, Jin-Kook; Ko, In-Yong (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
A dense nanocrystalline 5NbSi(2)-SiC-Si3N4 composite was synthesized by the pulsed current activated combustion synthesis (PCACS) method within 4 min in one step from mechanically activated powders of NbC, 4NbN and 14Si. A highly dense 5NbSi(2)-SiC-Si3N4 composite with a relative density of up to 98.5% was produced under the simultaneous application of a pressure of 60 MPa and an electric current. The average grain size and mechanical properties (hardness and fracture toughness) of the composite were investigated. (C) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: MECHANICAL-PROPERTIES; OXIDATION BEHAVIOR; PRESSURE; POWDERS